2015
DOI: 10.4152/pea.201505265
|View full text |Cite
|
Sign up to set email alerts
|

nionic Effect on the Acidic Corrosion of Aluminum and its Inhibition by Lupine Extract

Abstract: Corrosion behavior of aluminum in 0.1 M HCl, 0.1 M HClO4 and 0.05 M H2SO4 solutions was studied using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The results showed that the rate of corrosion of aluminum was arranged in the order: HCl > HClO4 > H2SO4. Lupine extract is an effective green inhibitor for the corrosion of aluminum in acidic solutions. The inhibition efficiency of the extract was found to increase with increasing the concentration of the extract. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…40,41 It is generally composed of at least 47 compounds, viz., protein up to 50%, lipids 20%, and 5% quinoline alkaloid, while lupanine is the most prevalent followed by multiflorane and sparteine. 42 The aqueous extract of lupine was previously investigated as a corrosion inhibitor by electrochemical, chemical, and surface techniques, while the outcomes confirmed that the lupine extract was an effective corrosion inhibitor to carbon steel 43 and stainless steel pitting corrosion in HCl solutions. 44 In the present investigation, a corrosion inhibition study has been designed and investigated by employing lupine-derived carbon quantum dots (LCQDs) from sustainable lupine seeds.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…40,41 It is generally composed of at least 47 compounds, viz., protein up to 50%, lipids 20%, and 5% quinoline alkaloid, while lupanine is the most prevalent followed by multiflorane and sparteine. 42 The aqueous extract of lupine was previously investigated as a corrosion inhibitor by electrochemical, chemical, and surface techniques, while the outcomes confirmed that the lupine extract was an effective corrosion inhibitor to carbon steel 43 and stainless steel pitting corrosion in HCl solutions. 44 In the present investigation, a corrosion inhibition study has been designed and investigated by employing lupine-derived carbon quantum dots (LCQDs) from sustainable lupine seeds.…”
Section: Introductionmentioning
confidence: 81%
“…Lupine was reported to exhibit several significant nutritional, pharmaceutical, and medical benefits due to the large number of compounds it contains. , It is generally composed of at least 47 compounds, viz., protein up to 50%, lipids 20%, and 5% quinoline alkaloid, while lupanine is the most prevalent followed by multiflorane and sparteine . The aqueous extract of lupine was previously investigated as a corrosion inhibitor by electrochemical, chemical, and surface techniques, while the outcomes confirmed that the lupine extract was an effective corrosion inhibitor to carbon steel and stainless steel pitting corrosion in HCl solutions …”
Section: Introductionmentioning
confidence: 95%
“…In the oil industry, the acidization of petroleum oil wells, an important stimulation technique, is used to enhance production [35]. HCl, HClO 4 and H 2 SO 4 are the most applied acidic solutions because of their highly corrosive nature with regard to many metals and alloys even at low concentrations [36], whereas HNO 3 and H 3 PO 4 are used occasionally. In this study, the inhibition efficiencies of polyvinylpyrrolidone are mainly applied in different acid media such as perchloric acid, The inhibitor molecules strongly interact with the metal surface in the presence of perchlorate ions due to the low coordination capacity of perchlorate ions.…”
Section: Effect Of the Acid Mediummentioning
confidence: 99%